Methodology of Estimation of Parameters in the Mechanism of Selecting Organizational and Technological Solutions - Ichetovkin, A. A (Science and Transport Progress, 2021)
Purpose. The aim of this study is the substantiation of the methodology for assessing the choice parameters of the organizational and technological solutions, the selection mechanism is based on and determining the expediency of a particular decision regarding the priority of certain parameters within the integrated approach taking into account the systemic effect. Methodology. According to the integrated approach, the mechanism for the optimal choice of the organizational and technological solutions should be based on certain parameters. The selection mechanism requires the use of models that take into account the synergistic effect of the following factors: efficiency increase of the activity as a result of integration, merging of individual parts into a single system due to the systemic effect based on the empirical method. The main role within the integrated approach belongs to the assessment of the parameters of organizational and technical solutions, which should be considered as one of the tools of integrated management. Findings. It was determined that the mechanism for selecting the organizational and technological solutions should take into account the use of technical solutions and individual design parameters of construction products in various environmental conditions, assess the risks inherent in the implementation of each organizational and technological solution, which increases its efficiency by taking into account the total risks. Proceeding from this, a methodology for the rapid assessment of the parameters of organizational and technological solutions has been substantiated. The methodology makes it possible to increase the efficiency of the mechanism for their selection by taking into account the total risks and to form a matrix for assessing typical organizational and technological solutions. An informational model of the process of choosing organizational and technological solutions according to the tasks of organizational and technological design is proposed. Originality. A substantiated methodology and information model for assessing the parameters of the choice of organizational and technological solutions is proposed, which is the basis for the development of algorithms for their assessment, based on certain parameters of the choice efficiency, from the standpoint of the influence of environmental factors, integral indicators, the likelihood of reliability of the implementation of the design quality parameters. Practical value. The results of the study help to make the process of developing organizational and technological solutions typical, while ensuring the ability to take into account all integral parameters of the impact, and environmental factors. The matrix for evaluating typical organizational and technological solutions can be used both at the level of a separate construction and design organization, and as the basis of an information system, or a program for automating the process of selecting organizational and technological decisions, which will speed up the process of analysis and adoption of such decisions, and increase the efficiency of the choice mechanism.